2019
DOI: 10.1016/j.ajic.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Infection free midline catheter implementation at a community hospital (2 years)

Abstract: Background: To reduce excess central line use and provide an option for difficult venous access patients through the introduction of a midline catheter. Methods: Design included prospective monitoring of the implementation of a quality improvement project. The setting was a 576 bed, urban, community, nonprofit, Magnet recognized, level 3 trauma center serving primarily adult patients. Midline and peripherally inserted central catheters were inserted by a specialty nursing team; care and maintenance of all devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 14 publications
5
67
1
1
Order By: Relevance
“…Symptoms of leaking, pain, and swelling are not complications in and of themselves, as is typically reported in the literature 31 , 32 , 40 , 41 ; they are signs of vessel damage and thrombosis, as evidenced by histopathological examination. Unlike with use of short peripheral i.v.…”
Section: Discussionmentioning
confidence: 66%
“…Symptoms of leaking, pain, and swelling are not complications in and of themselves, as is typically reported in the literature 31 , 32 , 40 , 41 ; they are signs of vessel damage and thrombosis, as evidenced by histopathological examination. Unlike with use of short peripheral i.v.…”
Section: Discussionmentioning
confidence: 66%
“…For hospitalized children and adolescents, PIVCs and midline catheters were reported as appropriate for short-term peripherally compatible therapies in multiple studies because of their low risk of catheter-related infections and thrombosis in comparison to PICCs. 14,43,94,100,127,143 However, in one study, the authors suggested that these devices are associated with increased risk of occlusion with extended dwell times. 127 PICCs were reported to have high insertion success rates 84 and low failure rates in children and adolescents, 6,59 although one study reported severe complications in 40.1% of failed PICCs, associated with increasing patient age.…”
Section: Figurementioning
confidence: 99%
“…Since publication, MAGIC has been implemented in many hospitals worldwide but particularly in the United States, with evidence suggesting significant reductions in inappropriate VAD use, patient harm, and costs. [9][10][11] Similar evidence-based VAD appropriateness criteria have not been developed for pediatrics. Therefore, we sought to develop the Michigan Appropriateness Guide for Intravenous Catheters in pediatrics (miniMAGIC), a pediatric-focused version of its adult counterpart, using the RAND Corporation and University of California, Los Angeles (RAND/ UCLA) Appropriateness Method 12 to address this knowledge gap.…”
mentioning
confidence: 99%